« Malthus in, Malthus out? » - Julien, Pierre-André; Freeman, Christopher (L'Actualité économique, 1974)
AbstractIn this paper, we analyse the world model which represents the most ambitious attempt yet to bring together six great forecasts comprising population, resource depletion, food supply, capital investment, pollution and space. We wish to show on the one hand that the model has serious limitations and, on the other, that many different conclusions can be arrived at with this kind of study.Firstly we attempt to demonstrate that the model structure is too rigid, containing too many constants; secondly we question the value of certain time series data; thirdly the two principal assumptions are discussed: the constant exponential trends of population and capital investment and the too long delays in the feedback processes that control the physical growth of the world system.For example Dennis Meadow et al. believe that all technological innovations will increase crowding and pollution. In concentrating on physical limits, they neglect changes in values which can change many trends or rate of trends.This is why we are saying "Malthus in, Malthus out". The model is the message and a great part of the results depends entirely on the quality of data, the rigidity of the model and on the limits of the assumptions.